Batch and Flow Injection Spectrophotometric Determination of Doxycycline Hyclate in Pharmaceutical Preparations - Al-Abachi, Mouayed Q; Al-Nedawi, Zaid A (Al-Nahrain Journal of Science, 2018)
New, simple and sensitive batch and flow injection spectrophotometric methods for the determination of doxycycline hyclate (DCH) in pharmaceutical preparations were developed. These methods were based on diazotization-coupling reaction between diazotized o-nitroanline (DONA) and DCH in sodium carbonate medium to form yellow-orange colored azo dye product has a maximum absorbance at 448 nm. Calibration graphs of absorbance versus concentration show that Beerʼs law were obeyed over the concentration ranges 0.4-52, 5-200 µg mL-1 of DCH, with limit of detection of 0.284, 1.117 µg mL-1 of DCH for batch and flow injection analysis (FIA) procedure respectively, and sample throughput was 171 h-1 for FIA method. All chemical and physical conditions affected on the developed colored product were carefully studied and the proposed methods were successfully applied for the determination of doxycycline in its pharmaceutical preparations.